2003
DOI: 10.1093/rheumatology/keg303
|View full text |Cite
|
Sign up to set email alerts
|

Health problems following Campylobacter jejuni enteritis in a Lancashire population

Abstract: A variety of health problems occur consistently following C. jejuni enteritis and substantially increase morbidity due to campylobacteriosis in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Infection can lead to serious sequelae such as Guillain-Barré syndrome and reactive arthritis [4]. Of the species pathogenic to humans, 90% of disease is caused by C. jejuni and most of the rest by C. coli [5].…”
Section: Introductionmentioning
confidence: 99%
“…Infection can lead to serious sequelae such as Guillain-Barré syndrome and reactive arthritis [4]. Of the species pathogenic to humans, 90% of disease is caused by C. jejuni and most of the rest by C. coli [5].…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter is a commensal constituent in the microflora of a wide range of animals, and has been isolated from numerous hosts including domestic and wild mammals, birds and reptiles [2-4]. In humans, however, Campylobacter is pathogenic, routinely causing acute diarrhoea and occasionally serious sequelae including Guillain-Barre Syndrome and reactive arthritis [5]. The majority of human campylobacteriosis is caused by C .…”
Section: Introductionmentioning
confidence: 99%
“…We observed that all 18S rRNA gene libraries generated in the current study were dominated by clones later identified as a solanaceous plant, perhaps that of a common agricultural weed in the study area (10). As plants have been shown to have between 500 and 40,000 copies of the 18S rRNA gene per diploid cell (73), a single contaminating cell could severely hinder the detection of protists. Our regimen for sample processing may have benefitted from a prefiltration step; however, it is uncertain if this would have impacted the recovery of large or attached protists.…”
Section: Discussionmentioning
confidence: 99%